IMPACT OF INTERNATIONALIZATION ON THE CAPITAL STRUCTURE OF COMMERCIAL COMPANIES (Polityki Europejskie, Finanse i Marketing)
International enterprises (in this paper, international companies are understood as companies that sell their products and services abroad) are precious for the national economy because, through their experience in international sales, they stimulate the development of other companies in the same industry and their subcontractors. The knowledge that these companies have gained on international markets through the spillover effect spreads on their suppliers, as well as through imitation or cooperation on their competitors. Also, international companies (in the meaning: domestic export companies) are often the first to use new technological solutions and product innovations, which contributes to the modernization of products in the entire business sector. Dynamic and robust international companies usually also build networks with entities from different countries in order to cooperate on development, negotiation, and sales, which also encourages similar activities of their competitors. For all these reasons, national governments should take action to help to export companies, or at least monitor the problems that such entities report. The purpose of the publication is to draw attention to the higher demand for the debt that exists in such enterprises and to discuss the reasons for this. In particular, the purpose of the publication was to verify 2 research hypotheses: H1: Internationalization increases indebtedness of a company measured with the debt to equity ratio, and H2: The scale of internationalization (measured with the share of foreign sales to total sales) is positively related to the level of indebtedness (measured with the debt to equity ratio). For both hypotheses we found no grounds to reject these hypotheses. In the opinion of the authors, the demand for debt from exporters should be monitored, especially in terms of the availability of this form of financing for exporters from the SME sector. The paper used the Arellano-Bond model and data downloaded from the Orbis database for years 2007 – 2017.